Eosinophilic gastroenteritis with multiple serous membrane effusion as the first sign: a case report and literature review. Issue 4 (April 2020) - Liang, Ma; Liwen, Zhang; Bingfang, Chen; Yanbo, Ding; Jianping, Chen
Multiple serous membrane effusion (MSSE) as the first sign of eosinophilic gastroenteritis is extremely rare, and its clinical features and treatment methods have not been well described. The clinical characteristics, diagnosis, and treatment methods of MSSE in a 44-year-old woman were retrospectively reviewed. Laboratory testing revealed an elevated eosinophil count and serum immunoglobulin E level. The levels of all tumor markers were normal, but the CA125 level in serum and ascitic fluid was significantly increased. Ultrasonography showed a large amount of ascites and a moderate amount of pleural effusion. Echocardiography showed a small amount of pericardial effusion. Chest and abdominal computed tomography showed gastrointestinal wall thickening. Moreover, eosinophilic infiltration was detected in duodenal and rectal biopsy samples that had been collected during endoscopic examination of the upper gastrointestinal system. The patient was treated with 30 mg of prednisolone, and seafood was excluded from her diet for 4 weeks. The prednisolone was tapered over 8 weeks and continued at 5 mg prednisolone daily thereafter. The MSSE and peripheral eosinophilia showed a dramatic response to the steroid treatment. This case indicates that we should be highly aware of MSSE as the first clinical manifestation of eosinophilic gastroenteritis.